2010
DOI: 10.1182/blood-2010-03-275446
|View full text |Cite
|
Sign up to set email alerts
|

Program death-1 signaling and regulatory T cells collaborate to resist the function of adoptively transferred cytotoxic T lymphocytes in advanced acute myeloid leukemia

Abstract: Tumor-induced immune defects can weaken host immune response and permit tumor cell growth. In a systemic model of murine acute myeloid leukemia (AML), tumor progression resulted in increased regulatory T cells (Treg) and elevation of program death-1 (PD-1) expression on CD8 cytotoxic T cells (CTLs) at the tumor site. PD-1 knockout mice were more resistant to AML despite the presence of similar percentage of Tregs compared with wild type. In vitro, intact Treg suppression of CD8 T-cell responses was dependent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
201
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 253 publications
(222 citation statements)
references
References 50 publications
8
201
0
2
Order By: Relevance
“…27 Conversely, the interaction of Treg PD-1 with PD-L1 inhibits the proliferation of Tregs in the liver of patients with chronic hepatitis C virus infection. 28 This finding, in conjunction with our results and others demonstrating a requirement for PD-1 in Treg function, [23][24][25] suggests dual and opposing functions for Treg PD-1; inhibiting the activity of target immune cells and restricting the proliferation of Tregs to fine-tune local immune responses.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…27 Conversely, the interaction of Treg PD-1 with PD-L1 inhibits the proliferation of Tregs in the liver of patients with chronic hepatitis C virus infection. 28 This finding, in conjunction with our results and others demonstrating a requirement for PD-1 in Treg function, [23][24][25] suggests dual and opposing functions for Treg PD-1; inhibiting the activity of target immune cells and restricting the proliferation of Tregs to fine-tune local immune responses.…”
Section: Discussionsupporting
confidence: 85%
“…Analysis of highly pure PD-1 is a negative costimulatory molecule upregulated on activated effector T cells that inhibits T cell receptor signaling, 22 but recent studies have also demonstrated that PD-1 is essential for Tregs to suppress both CD4 and CD8 T cell responses. [23][24][25] In our study, PD-1 blockade completely reversed any protection offered by Tregs, even if the Tregs had been preincubated with an A 2A R agonist.…”
Section: Discussionsupporting
confidence: 46%
“…9 For example, usually inhibitory signaling via PD-1 is reported altered to stimulatory signaling in Treg found in environments rich in suppressive factors such as tumor microenvironments. 33,34 Our data suggest that the same mechanisms of "reverse" signaling apply to Breg.…”
Section: Discussionmentioning
confidence: 65%
“…15 T-cell suppression preventing excessive inflammatory response at the site of chronic inflammation depends on an intact PD-1/PD-L1 axis. 16 In the presence of activated T cells, in return, tumor cells upregulate PD-L1, the major mediator of immunosuppression, resulting in inhibition of T helper cell response and "T-cell exhaustion" via the PD-1 pathway. 4 Targeting the immune system as novel therapeutic modality has proven efficacy in CRC.…”
Section: Introductionmentioning
confidence: 99%